Review of the green lacewing genus Apochrysa Schneider (Neuroptera: Chrysopidae) - Winterton, Shaun L.; Gupta, Ankita (Zootaxa, 2020)
Delicate green lacewings in the genus Apochrysa Schneider (Neuroptera: Chrysopidae: Apochrysinae) are reviewed with each species diagnosed and figured; a key to species is included.